Application of Usrah using Fuzzy Delphi Method in the Malaysian Professional Learning Community - Bin Yahya, Mohd Razi; Abdullah, Zuraidah (EARR (Educational Administration Research and Review), 2021)
The Professional Learning Community (KPP) is no stranger to Malaysia if the Malaysian Ministry of Education itself has taken the initiative to promote and implement it in the teacher learning culture in schools. However, it still remains with western characteristics and it is up to any group of teachers to realize it either in its original form or make some adjustments based on the local context in Malaysia. Research on the KPP has found that there are many similarities with the concept of usrah. However, there are slight differences between the two. Researchers see these similarities and differences as an advantage when these two concepts are combined. A structured interview has been carried out on thirteen experts in the fields of usrah and KPP. The results of this meeting have been described in five dimensions and their characteristics based on the characteristics of the module by Tengku Sarina Aini Fatimah Sahida (2018) which were adjusted, namely the dimensions of concept, content, leadership, assessment and initiative. A total of 70 traits have been identified and analyzed using the Fuzzy Delphi technique. In conclusion, 65 characteristics have been approved and agreed by a group of experts in combining KPP and usrah techniques among teachers in schools.